Numerical Simulation of Soil Water and Heat Transport with Different Vertical Discretization Schemes BCC_AVIM Land Surface Model - Zisha LIU; Shihua LÜ; Pengfei XU; Yiqun BAO; Huiqi YOU; Fan YANG (Gaoyuan qixiang, 2024)
The stratification of soil in land surface models is a crucial aspect that requires careful consideration.Typically， the surface layer of soil， which is significantly influenced by the atmosphere-ground interface， should be subdivided.Furthermore， as the soil goes deeper， the thickness of the soil layers can be increased accordingly.Previous studies have demonstrated that the thickness of soil below the root zone has varying effects on simulation results under different weather and climate integration conditions.Therefore， the soil stratification mode should be adjusted based on the research requirements.However， the optimal soil stratification mode in land surface models remains uncertain.This paper aims to explore the sensitivity of different soil vertical discretization schemes to the simulation of soil hydrothermal properties， surface radiation flux， sensible heat flux， and latent heat flux using the BCC_AVIM land surface model.The original scheme of soil stratification in the BCC_AVIM land model consists of 10 layers.In this study， the node depth， soil layer thickness， and interface depth of soil layers were interpolated from the original 10 layers to 20 layers， which is referred to as scheme 1.Additionally， the vertical soil discretization scheme in CLM5.0 was used as a reference and improved for the BCC_AVIM land model.Consequently， the original soil layer was increased from 10 to 20， which is referred as scheme 2.After comparing the results of the improved schemes 1 and 2 with those of the original scheme， it is evident that： （1） The simulation results of schemes 1 and 2 are more consistent with the measured data， and the simulation accuracy of the numerical value and changing trend of soil temperature in each layer is improved.Scheme 1 performs better in simulating shallow soil temperature.（2） The three schemes have good simulation effects on shallow soil moisture， but relatively poor simulation effects on deep soil moisture.The simulation of the variation trend and numerical value of soil moisture curve in each layer in Scheme 1 is closer to the measured data.（3） Scheme 1 is more reasonable in determining whether each layer of soil freezes or melts， which is closer to the measured data.Overall， Scheme 1 has the best simulation effect.Therefore， it can be concluded that the simulation effect of the first scheme is improved compared to the original scheme， indicating that denser and more detailed soil stratification under the same soil depth is beneficial in improving the simulation ability of the model for soil water and heat transport.Additionally， the simulation effect of scheme 1 is generally better than that of scheme 2， indicating that the shallow middle layer with more dense soil stratification under the same soil level has a positive impact on improving the simulation ability of the model on soil water-heat transport.